Arthroscopic Treatment and Prognostic Classification of Anterior Soft Tissue Impingement of the Ankle. (January 2016) - Buda, Roberto; Baldassarri, Matteo; Parma, Alessandro; Cavallo, Marco; Pagliazzi, Gherardo; Castagnini, Francesco; Giannini, Sandro
Background: Anterior soft tissue impingement of the ankle has been described based on the etiology and location, but no classification has been reported. Arthroscopic treatment is usually considered effective, even if the behavior of the different forms of impingement is not clear. The purpose of this study was to analyze the factors affecting long-term results. Methods: Forty-two patients with a mean age of 32.6 years were arthroscopically treated between 2004 and 2008. Impingement lesions were identified according to clinical examination and confirmed by MRI. Soft tissue impingement was detected and classified according to location (anteromedial, anterolateral, syndesmotic or diffuse). Patient data, foot morphology, and previous trauma or surgery were recorded. Patients were evaluated after a mean of 90.1 months' follow-up with the American Orthopaedic Foot & Ankle Society (AOFAS) scoring system. Results: The mean AOFAS score improved from 40.6 preoperatively to 82.6, 78.4, and 74.8, respectively, at the 2-, 4-, and 6-year follow-ups ( P < .05). The anterolateral form showed higher scores compared to the diffuse or anteromedial forms. Age, foot morphology, and previous trauma or surgery did not affect the results. Body mass index of more than 26 and male gender were associated with worse outcomes. Conclusion: Arthroscopic debridement proved effective in the treatment of soft tissue impingement. Furthermore, we were able to classify the location of the anterior soft tissue impingement of the ankle, which may have prognostic importance. Level of Evidence: Level IV, case series.